2022
DOI: 10.3390/v14102227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Five Buffers for Inactivation of Monkeypox Virus and Feasibility of Virus Detection Using the Panther Fusion® Open Access System

Abstract: Rapid diagnosis is key to containing viral outbreaks. However, for the current monkeypox outbreak the major deterrent to rapid testing is the requirement for higher biocontainment of potentially infectious monkeypox virus specimens. The current CDC guidelines require the DNA extraction process before PCR amplification to be performed under biosafety level 3 unless vaccinated personnel are performing assays. This increases the turn-around time and makes certain laboratories insufficiently equipped to handle spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…While the virus is endemic to Central and West Africa [2,3], the United States is the most affected, which has reported around 27,000 cases. The Center for Disease Control and Prevention (CDC) had to raise the alert level by declaring the disease a public health emergency [4,5]. The connectivity the US has with other parts of the world socially and economically implies that it may be a matter of time before the disease spreads even further.…”
Section: Introductionmentioning
confidence: 99%
“…While the virus is endemic to Central and West Africa [2,3], the United States is the most affected, which has reported around 27,000 cases. The Center for Disease Control and Prevention (CDC) had to raise the alert level by declaring the disease a public health emergency [4,5]. The connectivity the US has with other parts of the world socially and economically implies that it may be a matter of time before the disease spreads even further.…”
Section: Introductionmentioning
confidence: 99%
“…The Panther Fusion system open access channel has previously been utilized in direct detection or characterization of bacterial ( 41 ), parasitic ( 41 ), and viral ( 42 46 ) agents of disease and was posited in this study as an automated option for MRM determination within primary specimens testing positive for M. genitalium rRNA. Initial experimentation revealed that incubation of IVT wild-type 23S rRNA with high-concentration MRM primer and detection probe sequences, as well as an increased concentration of MgCl 2 , resulted in a propensity toward false-detections of macrolide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although literature data on inactivation methods were previously only available for VACV and VARV viruses among the OPVs, recent research by Batejat et al in 2022 on MPXV recom-mends a 30-minute treatment at 60 °C for the Clade II and Clade I genetic lineages using viral transport media (VTM) and FBS (97). Further evaluation of heat treatment under different conditions (30 minutes at 65 °C, 15 minutes at 65 °C, or 15 minutes at 95 °C) by Fischer in 2022 revealed no plaque formation after such a procedure, providing viable protocols for MPXV inactivation (98). Of note, heat treatment at 60, 70, or 95 °C only minimally affected the detection of MPXV DNA by qPCR, indicating that inactivated samples are suitable for molecular diagnostics without a significant decrease in Ct values (97).…”
Section: Mpxv Inactivationmentioning
confidence: 99%
“…In addition, evaluations of commonly used reagents in clinical laboratories such as Trizol and commercially available lysis buffer AVL with ethanol were performed, showing inactivation of MPXV after a 10-minute incubation at room temperature (98). A study testing seven commercial diagnostic buffers confirmed inactivation of MPXV at different incubation times, and heat (56 °C and 60 °C) and sodium dodecyl sulfate detergent were also found to be effective, highlighting the importance of matching the protocol to downstream biological processes (99).…”
Section: Mpxv Inactivationmentioning
confidence: 99%